Flow Chemistry for the Synthesis of Heterocycles (Topics in Heterocyclic Chemistry, 2018)
This volume provides an overview of recent developments and scope in the use of flow chemistry in relevance to heterocyclic synthesis. The heterocyclic ring is the most prominent structural motif in the vast majority of natural products as well as pharmaceutical compounds since this facilitates tuneable interactions with the biological target besides conferring a degree of structural and metabolic stability. In recent times, flow chemistry has heralded a paradigm shift in organic synthesis as it offers several unique advantages over conventional methods like drastic acceleration of sluggish transformations, enhanced yields, cleaner reactions etc and is gradually gaining a lot of attention among organic chemist worldwide. Given the importance of heterocycles in natural products, medicinal chemistry and pharmaceuticals, this is a well warranted volume and complements the previous volume of Topics in Organometallic Chemistry 'Organometallic Flow Chemistry'. This volume offers a versatile overview of the topic, besides discussing the recent progress in the flourishing area of flow chemistry in relevance to heterocyclic chemistry; it will also help researchers to better understand the chemistry behind these reactions. This in turn provides a platform for future innovations towards the designing of novel transformations under continuous flow. Thus, this volume will appeal to both the novices in this field as well as to experts in academia and industry.